Complete Genome Sequence of a Novel Genotype of Pepper Mild Mottle Virus Infecting Pepper in Chile - Berendsen, Sven M. H. (Microbiol Resour Announc, 2020)
The complete genome sequence of a Pepper mild mottle virus (PMMoV) found on pepper seeds produced in Chile in 2019 was determined using Oxford Nanopore Technologies and Sanger sequencing. The low nucleotide sequence identities (between 89% and 91%) to known PMMoV isolates suggested that this isolate belongs to a novel genotype.